Immersive journalism: A study on 360-degree news - DAS, Nanda S; SreedhararN, N.V (International Journal of Psychosocial Rehabilitation, 2020)
The increasing influence of media in society has forced the journalists to adopt a new innovation in the presentation of news stories and the most pristine innovation among them is immersive journalism with the 360-degree news being a subcategory of it. Here they cover a 360-degree view of a video and thereby the audience get a first-person experience of the incident or circumstances in the news stories with head-mounted display. This research paper uses qualitative content analysis along with a focus group discussion among college goings tudents to understand their perception towards 360-degree news. The inference drawn from the study implies that immersive journalism has huge acceptance among audience and have a stable future in journalism